Palmitate is not an effective fuel for pancreatic islets and amplifies insulin secretion independent of calcium release from endoplasmic reticulum. Issue 3 (4th May 2019) - Kuok, Iok Teng; Rountree, Austin M.; Jung, Seung-Ryoung; Sweet, Ian R.
ABSTRACT: The aim of the study was to determine the acute contribution of fuel oxidation in mediating the increase in insulin secretion rate (ISR) in response to fatty acids. Measures of mitochondrial metabolism, as reflected by oxygen consumption rate (OCR) and cytochrome c reduction, calcium signaling, and ISR by rat islets were used to evaluate processes stimulated by acute exposure to palmitic acid (PA). The contribution of mitochondrial oxidation of PA was determined in the presence and absence of a blocker of mitochondrial transport of fatty acids (etomoxir) at different glucose concentrations. Subsequent to increasing glucose from 3 to 20 mM, PA caused small increases in OCR and cytosolic calcium (about 20% of the effect of glucose). In contrast, the effect of PA on ISR was almost 3 times that by glucose, suggesting that the metabolism of PA is not the dominant mechanism mediating PA's effect on ISR. This was further supported by lack of inhibition of PA-stimulated OCR and ISR when blocking entry of PA into mitochondria (with etomoxir), and PA's lack of stimulation of reduced cytochrome c in the presence of high glucose. Consistent with the lack of metabolic stimulation by PA, an inhibitor of calcium release from the endoplasmic reticulum, but not a blocker of L-type calcium channels, abolished the PA-induced elevation of cytosolic calcium. Notably, ISR was unaffected by thapsigargin showing the dissociation of endoplasmic reticulum calcium release and second phase insulin secretion. In conclusion, stimulation of ISR by PA was mediated by mechanisms largely independent of the oxidation of the fuel.